2006
DOI: 10.1590/s0066-782x2006000600004
|View full text |Cite
|
Sign up to set email alerts
|

Influência da redução da pré-carga sobre o índice de desempenho miocárdico (índice de Tei) e outros parâmetros Doppler ecocardiográficos da função ventricular esquerda

Abstract: The Tei index was affected by hemodialysis-induced preload alterations, as well as other mitral inflow Doppler-derived parameters. The diastolic parameters of mitral annulus Doppler tissue were independent of preload, while systolic velocities suggested improved systolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…Although this conclusion comes from data derived from conventional Doppler mitral flow (known to be dependent on preload), our study showed only a marginal variation in the E'/A' ratio, this obtained by tissue Doppler and less susceptible to loading status 9 . Thus, on the one hand there may have been an insufficient number of cases to demonstrate significant differences in the E' and A' velocities that would corroborate the hypothesis of actual diastolic dysfunction, but, on the other hand, the decrease in E/A ratio after exercise may simply correlate with preload reduction.…”
Section: Passaglia Et Al Effects Of Prolonged Physical Exercisecontrasting
confidence: 69%
See 1 more Smart Citation
“…Although this conclusion comes from data derived from conventional Doppler mitral flow (known to be dependent on preload), our study showed only a marginal variation in the E'/A' ratio, this obtained by tissue Doppler and less susceptible to loading status 9 . Thus, on the one hand there may have been an insufficient number of cases to demonstrate significant differences in the E' and A' velocities that would corroborate the hypothesis of actual diastolic dysfunction, but, on the other hand, the decrease in E/A ratio after exercise may simply correlate with preload reduction.…”
Section: Passaglia Et Al Effects Of Prolonged Physical Exercisecontrasting
confidence: 69%
“…The intraobserver variability for echocardiographic variables evaluated in this study has been previously published by our group 8,9 .…”
Section: Echocardiographymentioning
confidence: 96%
“…It should be emphasized that DE can reveal clinically hidden ventricular dysfunctions by determining the ratios between systolic and diastolic ventricular measurements (diameter, area, volume) 11 . It is also said that the TEI index can assess the ventricular systolic function 3,19 . DE can also offer information that helps detect pulmonary hypertension 7 and forecast survival 14 in rats.…”
mentioning
confidence: 99%
“…It is vital to determine the volume to be taken for ultrafiltration (10) . Through dry weight, residual diuresis and the amount of hydric intake, the nurse controls the hydric balance and evaluates the patients hydration.…”
Section: Resultsmentioning
confidence: 99%